Problems screening for HAND among the educationally disadvantaged. Issue 2 (4th March 2018) - Musso, Mandi W.; Cosgrove, Seandra J.; Peltier, MacKenzie R.; McGee, Brian L.; Jones, Glenn N.
ABSTRACT: Neurocognitive screeners are used to detect symptoms of HIV-Associated Neurocognitive Disorders (HAND). However, the degree to which education and socioeconomic status affect these screeners remains unclear. Neurocognitive screeners were administered to 187 socioeconomically disadvantaged HIV+ individuals upon entering treatment who had no other risk factors for HAND. The false positive rates were: 84% for the Montreal Cognitive Assessment, 59% for the International HIV Dementia Scale, and 28.3% for the Modified HIV Dementia Scale. Given these high false positive rates, the screeners may be more useful for establishing baseline functioning and sequential testing to detect deterioration.